A comparison of dropout rate of three commonly used single cell RNA-sequencing protocols - Omar Alaqeeli (Biotechnology & Biotechnological Equipment)
Dropout is an inevitable event in the RNA sequencing process and it is sometimes mistaken with gene inactivity. Here we compare three sequencing protocols, SMARTer, Smart-Seq and Tang, in terms of their dropout rate using 33 datasets that contain 689 million gene abundance reads. We found that SMARTer has the lowest dropout rate with 64.51% across all its gene abundance reads. Smart-Seq comes next with 72.59% and lastly Tang with 79.90%. Thus, SMARTer has the highest reliability when it comes to detecting gene abundance. Furthermore, the dropout rate among all three sequencing protocols increases ascendingly as the sequencing protocol proceeds further in scanning gene abundance. This suggests that the ability to detect gene abundance drops as the sequencing protocol advances thus reliability decreases.